Seni Kulinari, Kekuasaan, dan Multikulturalisme dalam Master Cooking Boy/ The Real Master Cooking Boy Karya Etsushi Ogawa - Kurnia, Lilawati (UI Scholars Hub, 2006)
This essay examines manga, the japanese comic Master Cooking Boy